Perilaku Aparatur Dalam Pelayanan Administrasi Kependudukan di Kabupaten Bone - A. Ishaq Alfarizi Jamal (Departemen Ilmu Pemerintahan Fisip Unhas, 2026)
Population administration services constitute an essential form of public service aimed at ensuring citizens' civil rights. The quality of these services is highly influenced by the behavior of public officials who deliver them. This study aims to analyze the behavior of public officials in population administration services at the Department of Population and Civil Registration of Bone Regency, focusing on the dimensions of care, discipline, and responsibility. This research employed a qualitative approach with a descriptive research design. Data were collected through in-depth interviews, observation, documentation, and literature review. The informants consisted of service officers, structural officials, and members of the public who utilized population administration services. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that the behavior of public officials has a significant influence on the quality of population administration services. Care is reflected in officials’ empathy, responsiveness to public needs, and ability to provide clear service information. Discipline is demonstrated through compliance with working hours, adherence to service procedures, and commitment to delivering services on time. Meanwhile, responsibility is reflected in the officials’ seriousness in completing tasks, maintaining service quality, and ensuring that citizens receive their administrative rights accurately and efficiently. These three dimensions are fundamental in creating population administration services that are effective, efficient, and oriented toward public satisfaction.